N-Acylethanolamine Acid Amidase contributes to disease progression in a mouse model of multiple sclerosis. (October 2020) - Pontis, Silvia; Palese, Francesca; Summa, Maria; Realini, Natalia; Lanfranco, Massimiliano; De Mei, Claudia; Piomelli, Daniele
Graphical abstract: Highlights: NAAA terminates the biological actions of PEA, an endogenous PPAR-α agonist. Spinal cord NAAA expression is enhanced in the EAE mouse model of multiple sclerosis. In the same model, genetic NAAA deletion attenuates disease progression. Conversely, NAAA overexpression in monocyte-derived cells aggravates EAE. NAAA-regulated PEA signaling may be a central control point for neuroinflammation. Abstract: N -Acylethanolamine acid amidase (NAAA) deactivates the endogenous peroxisome proliferator-activated receptor-α (PPAR-α) agonist palmitoylethanolamide (PEA). NAAA-regulated PEA signaling participates in the control of peripheral inflammation, but evidence suggests also a role in the modulation of neuroinflammatory pathologies such as multiple sclerosis (MS). Here we show that disease progression in the mouse experimental autoimmune encephalomyelitis (EAE) model of MS is accompanied by induction of NAAA expression in spinal cord, which in presymptomatic animals is confined to motor neurons and oligodendrocytes but, as EAE progresses, extends to microglia/macrophages and other cell types. As previously reported for NAAA inhibition, genetic NAAA deletion delayed disease onset and attenuated symptom intensity in female EAE mice, suggesting that accrued NAAA expression may contribute to pathology. To further delineate the role of NAAA in EAE, we generated a mouse line that selectively overexpresses the enzyme in macrophages, microglia and other monocyte-derived cells. Non-stimulated alveolar macrophages from these Naaa CD11b+ mice contain higher-than-normal levels of inducible nitric oxide synthase and display an activated morphology. Furthermore, intranasal lipopolysaccharide injections cause greater alveolar leukocyte accumulation in Naaa CD11b+ than in control mice. Naaa CD11b+ mice also display a more aggressive clinical response to EAE induction, compared to their wild-type littermates. The results identify NAAA as a critical control step in EAE pathogenesis, and point to this enzyme as a possible target for the treatment of MS.